The Effect of Non-Debt Tax Shield and Corporate Tax Rate on Capital Structure in Healthcarecare Sector Companies Listed on the IDX - Patma Ayu; Beby Hilda Agustin; Ahmad Yani (LP2M IAIN Palopo, 2026)
This research investigates how the non-debt tax shield and corporate tax rate shape a firm's capital structure. As a fundamental financial policy, capital structure determines the composition of financing sources employed to sustain corporate operations and long-term growth. Variations in both the non-debt tax shield and the corporate tax rate are regarded as influential determinants capable of altering financing decisions. A quantitative descriptive design was implemented, whereas multiple linear regression analysis in SPSS served to examine the associations among the investigated variables. Empirical findings indicate that the non-debt tax shield exerts a statistically significant influence on capital structure. In contrast, no meaningful effect was identified between the corporate tax rate and the firm's capital structure. The findings of this research are expected to be considered for management in formulating more optimal funding policies and for future researchers in developing research related to factors that affect capital structure.